Literature on Adam and Eve : collected essays - Anderson, Gary A., 1955-; Stone, Michael E., 1938-; Tromp, Johannes (Brill, 2000)
For many centuries, the acts and destinies of the first-created human beings, Adam and Eve, have intrigued artists, story-tellers and theologians alike. This volume is a collection of articles on these traditions, written by some of the foremost scholars in the field. The volume consists of two parts. In the first part G.A. Anderson and M.E. Stone have combined a number of studies on the rich variety of Adam and Eve-traditions, from the Life of Adam and Eve onwards to late medieval writings in Armenian. The second part, edited by Johannes Tromp, consists of papers read at the 1998 Leiden symposium, and deals more specifically with the Life of Adam and Eve.
Keywords: Life of Adam and Eve -- Criticism, interpretation, etc.; Vie d'Adam et Ève -- Critique, interprétation, etc.; Life of Adam and Eve; Adam und Eva.; RELIGION -- Biblical Studies.; Aufsatzsammlung; Leven van Adam en Eva (apocrief); Criticism, interpretation, etc.